The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
The Glasgow Naturalist 2018
DOI: 10.37208/tgn27s09
|View full text |Cite
|
Sign up to set email alerts
|

Linking water quality with amphibian breeding and development: a case study comparing natural ponds and Sustainable Drainage Systems (SuDS) in East Kilbride, Scotland

Abstract: Amphibians have declined due to habitat loss and alteration. Sustainable Drainage Systems (SuDS) provide potential habitat for amphibians in urban landscapes. However, the contaminants they accumulate may cause increased pollutant exposure, and limited research has addressed whether differences in water quality between SuDS and natural ponds might restrict their use by amphibians. This study aimed to explore the effects of water quality on amphibian breeding and development in SuDS and natural ponds in East Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Although biodiversity enhancement is not the prime motivation behind SuDS installation, there is growing evidence that they can provide habitat for a wide range of wild species, amphibians included. Scottish studies include: O'Brien, ; O'Brien, Hall, Miro, Rae, & Jehle, ; Miro, Hall, Rae, & O'Brien, ; and Bird et al, . Hassall and Anderson () have reported similar results from Canadian urban storm‐water management ponds.…”
Section: Protection Enhancement and Mitigationmentioning
confidence: 89%
See 2 more Smart Citations
“…Although biodiversity enhancement is not the prime motivation behind SuDS installation, there is growing evidence that they can provide habitat for a wide range of wild species, amphibians included. Scottish studies include: O'Brien, ; O'Brien, Hall, Miro, Rae, & Jehle, ; Miro, Hall, Rae, & O'Brien, ; and Bird et al, . Hassall and Anderson () have reported similar results from Canadian urban storm‐water management ponds.…”
Section: Protection Enhancement and Mitigationmentioning
confidence: 89%
“…In the Pyrenees, Miro, Sabas, and Ventura () found a strong negative association between introduced trout and four out of six amphibian species, especially the common frog, but also that some amphibians could co‐exist with fish. In Scotland also, research has shown that some amphibians are capable of breeding successfully in the presence of at least some species of fish (Bird, Paterson, Downie, & Mable, ).…”
Section: Threatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of biochemical and histopathological changes in Indian frog caused by metal contamination can also be found in Jayawardena et al [189]. Bird et al [190] have however highlighted that the effect of metals on amphibians depends on the combination of metals present. Some of these effects are presented in Table 5.…”
Section: Mozambique Tilapia (Oreochromis Mossambicus) Common Carp (Cy...mentioning
confidence: 98%